Nursing Students' Attitudes Toward Artificial Intelligence, Technology, and Internet Addiction: A Descriptive and Relational Study. - Annak, İnci Mercan; Bütün, Cemile Gül; Dede, Döndü; Gülüç, Sudenur (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2026)
Background: The increasing integration of artificial intelligence (AI) in healthcare has highlighted the importance of nursing students’ attitudes toward these technologies. In this context, technology and internet addiction may act as influential factors shaping these attitudes. Aim: This study aimed to determine the levels of technology addiction, internet addiction, and attitudes toward AI among nursing students, and to examine the relationships between these variables. Methods: This descriptive and correlational study was conducted with 608 nursing students enrolled at the Faculty of Nursing of Gazi university. Data were collected face-to-face. The Spearman correlation test, Mann-Whitney U test, and Kruskal-Wallis H test were used for data analysis. Results: The mean age of the students was 20.72±2.11 years; 84.0% were female, 28.9% were first-year students, and 37.5% had a moderate grade point average (GPA) (2.50–3.00). AI was used by 84.4% of the students, primarily for homework (56.5%). A strong positive correlation was found between internet addiction and technology addiction, whereas negative attitudes toward AI were weakly and negatively correlated with these addictions. Male students had higher technology addiction scores, and AI users demonstrated significantly more positive attitudes toward AI. Conclusion: The majority of nursing students reported using AI, primarily for homework purposes. They demonstrated low levels of internet addiction and moderate levels of technology addiction. These findings suggest that the conscious and ethical use of AI should be promoted in nursing education, along with increased awareness initiatives addressing technology addiction.